PERBANDINGAN EFEKTIVITAS CEFTRIAXONE DAN CEFOTAXIME PADA PASIEN ANAK DEMAM TIFOID DI RUMAH SAKIT MITRA SIAGA - Anggy Rima Putri; Rosaria Ika Pratiwi (Jurnal Ilmiah Manuntung: Sains Farmasi Dan Kesehatan, 2022)
Ceftriaxone and cefotaxime are the antibiotics of choice for the treatment of typhoid fever. The effectiveness of antibiotics can be seen based on the length of stay in the hospital. This study aims to determine the characteristics of children with typhoid fever and the comparison of the effectiveness of ceftriaxone and cefotaxime on the length of stay in children with typhoid fever at Mitra Siaga hospital. The study was an observational analytic study with a sample of 100 medical records for children with typhoid fever who had met the inclusion and exclusion criteria. The effectiveness analysis was processed using the Mann-Whitney method. The results showed that the characteristics of the children with typhoid fever were 43% female (43 people) and 57% male (57 people), 52% (52 people) patients aged 1-7 years, and 48% (48 people). aged 8-14 years, length of stay 2 days 5% (5 people), 3 days 48% (48 people), 4 days 37% (37 people), 5 days 6% (6 people), 6 days 2% (2 person), 7 days 1% (1 person), and 8 days 1% (1 person). There was no difference in the effectiveness of ceftriaxone and cefotaxime on length of stay in patients with typhoid fever at Mitra Siaga hospital (P = 0.997> 0.05).